PRODUCTION OF INSULATION BOARDS BASED ON CRUSHED COTTON AND CEMENT - Turapov Farkhod Khursanovich (American Journals, 2023)
High-quality production of traditional building materials on a scientific basis, adaptation of their creation technologies to modern requirements, development of cheap, economical, high-quality materials and technologies, acquisition of new and refined materials, creation of their cost-effective technologies, repair and reconstruction of buildings and structures Perfection of production methods and effective use of materials in this process are important issues